Analysis of the Task of Writing English Textbooks for the 2013 Curriculum for Grade X of Senior High School Published by the Minister of Education and Culture Based on Paul Nation's Theory - Farikhah, Siti Laelatul; Mahbubah, Fina Saffanatul (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: This study aims to (1) describe writing assignments in the 2013 Curriculum *English* textbook for grade X students based on Paul Nation's theory, and (2) evaluate the suitability of the writing assignments in the book with the criteria suggested by Paul Nation. This study uses a descriptive method. Methodology: In this research, the writer employs descriptive research. This research uses the content analysis. The method of collecting data is comparing method and analyzing document by selecting the writing tasks on the textbook entitled Bahasa Inggristextbook for the tenth grade students of senior high school that meet the criteria of writing task suggested by Paul Nation. Main Findings: The results of the study showed that the writing tasks in English textbooks for grade X students met Paul Nation's criteria, with the distribution of Experience Task (22.22%), Shared Task (11.11%), Guided Task (59.25%), and Independent Task (7.40%). The total percentage reached 54.17%, meeting the standards proposed by Arikunto. This textbook is categorized as good and suitable for use by grade X students because it has met the recommended writing task criteria.. Novelty/Originality of this study: This study analyzes writing tasks in English textbooks of the 2013 Curriculum for senior high school students in grade X based on Paul Nation's theory, revealing the compatibility of the curriculum with current learning theories. The results provide insights to improve the effectiveness of English learning materials and assessments.